ESTUDO DA INFLUÊNCIA DO FENÔMENO DA DELAMINAÇÃO NA TENACIDADE À FRATURA DE AÇOS API 5L X60 E X70 EM ESPÉCIMES SE(T) - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
In this work the ductile crack growth resistance curves (J-R curves) was evaluated for the steels used in the oil and gas pipelines from the X60 and X70 API 5L grades using the unloading compliance technique. The non standardized SE (T) specimens were used due to the same has low constraint, it is feature of pipelines. The plastic area for the obtaining the J integral was performed by measuring from the crack mouth open displacement, (CMOD). The central emphasis this research was evaluated the delamination phenomenon influence from the fracture toughness and along the J-R curve. As also the microtexture in close to delamination and ductile fracture regions, by using the Electron Backscatter Diffraction (EBSD) technique. The results have shown that value average of 355kJ/m2 was similar for both the shallow and deep crack specimens. The J-R curve values average from the shallow crack specimens have displayed most steep J-R curves, namely, it obtained higher energy values along the ductile crack propagation. Specimens that showed delaminations, during fracture process, obtained higher energy values along the ductile crack propagation. The occurrence of delaminations was more common in deep crack specimens. The microtexture results have shown a random grain sizes distribution. The components with higher intensity in the delamination region were α-fiber textures: {113} <110>, {112} <110>, {223} <110> the same cause anisotropy of mechanical properties and can be influenced out-of-plane constraint during the test. Moreover, there was the occurrence of the {100} <110> recrystallization texture component, which have deleterious effect in occurrence of delamination in microalloyed steels. Whereas in the ductile fracture region occurred the {111} <231>, {111} <132> and {111} <123> γ-fiber, which it can be influenced the ductile crack propagation process.
Keywords: aços API X60 e X70; curvas J-R; espécime SE(T); delaminação; orientação cristalográfica; EBSD; API X60 and X70 steels; J-R curves; SE(T) specimen; delamination; crystallographic orientation; EBSD; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA